Preservation Yellow Alkaline Noodles Using Different Radiation Technologies - Soraya, Anissa (2011)
Yellow alkaline noodles (YAN) are very susceptible to spoilage. Currently, boric acid, a carcinogenic compound, was commonly applied as YAN preservative. The present study was conducted to investigate feasible radiation technologies to produce preservative-free yet long life YAN. These included applying gamma irradiation to improve the microbiological quality of wheat flour which was used as the main raw material, and post processing treatment using combination of microwave (MW) and pulsed-Ultra Violet (pulsed-UV) to reduce the microbiological contamination of YAN. Wheat flour for making noodles was irradiated using a 60Co Gamma ray at six different doses (0, 2, 4, 6, 8 and 10 kGy). The chemical composition, physicochemical properties, and microbiological quality of wheat flour were analysed. The irradiated flours were used for making YAN. The colour quality, textural properties, cooking quality, and the microbiological quality of YAN were analysed. Gamma irradiation did not cause any significant (P > 0.05) change on the chemical composition of wheat flour, whereas it caused significant changes (P < 0.05) in the physicochemical properties of wheat flour and YAN made from it. Gamma irradiation significantly (P < 0.05) reduced total microorganism load in wheat flour and YAN. All textural parameters of YAN were significantly (P < 0.05) affected by irradiation, except for springiness. In term of cooking quality, the cooking time was unaffected by irradiation, whereas cooking loss were significantly (P < 0.05) increased as the irradiation dose was increased. These findings confirmed that gamma irradiation was effective in reducing the microorganism load in wheat flour but it affected the physicochemical properties of wheat flour and resulted in undesirable textural properties and cooking quality of YAN. Therefore, this treatment was not applied in further study. Spoilage of YAN might also be caused by cross contamination from the environment during noodles preparation. Therefore, the post-processing decontamination treatment is deemed necessary. Combination of pulsed-UV and microwave treatment was chosen to reduce the microorganism load in YAN. Factorial design was employed to study the effect of microwave heating time at a power of 900 W (2450 MHz) and pulsed-UV energy level on the microbiological quality and textural properties of YAN. Twenty combinations of different microwave heating times (0 to 10 s) and pulsed-ultra violet energy level (0 to 7 J/cm2) were applied on the parboiled YAN. The response optimiser was applied to determine the optimum combination of these technologies in reducing the microorganism load in YAN without causing detrimental effects in the textural properties.The results of this study showed that the optimum combination is 5 s of microwave at power of 900 W (2450 MHz) followed by 3.5 J/cm2 pulsed-UV treatment. YAN was treated using the optimum combination of microwave and pulsed-UV and stored at ambient (28±2 oC) and chilled (4±2 oC) temperature. The results showed that the shelf life of treated YAN at ambient and chilled temperatures were 1.5 days and 3.6 weeks, respectively, while, the shelf life of untreated YAN (control) at ambient and chilled temperatures were 0.5 day and 2 weeks, respectively. In general, it can be concluded that gamma irradiation in the dose tested is not feasible for the decontamination of wheat flour. Meanwhile, application of combination microwave heating followed by pulsed-UV treatment was found to be effective in reducing the microorganism load in YAN. Combination of this treatment with chilled storage could further improve the YAN shelf life. A new processing method for extending the shelf life of preservative-free YAN was discovered and it can be proposed as an alternative processing method to replace the current practices.